The 7th International Electronic Conference on Water Sciences - Loukas, Athanasios (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book is the proceedings of the 7th International Electronic Conference on Water Sciences (ECWS-7), held online 15-30 March 2003, promoted by the open access MDPI journal Water (ISSN 2073-4441; IF 3.530). The title of ECWS-7 was "Adaptive Water Resources Management in an Era of Changing Climatic, Environmental and Social Conditions". This book of proceedings includes 102 papers, internationally and independently reviewed and presented in the conference. The topics of the papers cover a large number of subjects including Sustainable Water Resources Management, Water Resource Policy and Governance Hydrology, and Climate Change: Impacts on Water Resources and Hydrology.